A study on the effectiveness of global zakat game (gzg) as a zakat teaching and learning tool - Ab Rahman, Azman; Zainuddin, Nurkhamimi; Sahrir, Muhammad Sabri; Abd Khafiz, Hasanah (The Islamic Cutural Centre and London Central Mosque, UK, 2019)
Islamic Quarterly, 2019, 63(2), pp. 217–232